Differential profiles in auditory social cognition deficits between adults with autism and schizophrenia spectrum disorders: A preliminary analysis. (August 2016) - Tobe, Russell H.; Corcoran, Cheryl M.; Breland, Melissa; MacKay-Brandt, Anna; Klim, Casimir; Colcombe, Stanley J.; Leventhal, Bennett L.; Javitt, Daniel C.
Abstract: Impairment in social cognition, including emotion recognition, has been extensively studied in both Autism Spectrum Disorders (ASD) and Schizophrenia (SZ). However, the relative patterns of deficit between disorders have been studied to a lesser degree. Here, we applied a social cognition battery incorporating both auditory (AER) and visual (VER) emotion recognition measures to a group of 19 high-functioning individuals with ASD relative to 92 individuals with SZ, and 73 healthy control adult participants. We examined group differences and correlates of basic auditory processing and processing speed. Individuals with SZ were impaired in both AER and VER while ASD individuals were impaired in VER only. In contrast to SZ participants, those with ASD showed intact basic auditory function. Our finding of a dissociation between AER and VER deficits in ASD relative to Sz support modality-specific theories of emotion recognition dysfunction. Future studies should focus on visual system-specific contributions to social cognitive impairment in ASD.